2022
DOI: 10.37908/mkutbd.1009679
|View full text |Cite
|
Sign up to set email alerts
|

Determining effects of foliar boron applications on yield and fruit quality of apricot trees for reducing water stress

Abstract: Aims: The research was carried out to determine the effects of different boron doses on yield, yield components and quality on 5-6 years old apricot trees of Mogador variety, which were exposed to water stress in the Amik Plain in 2019. Methods and Results: The factorial experimental design was conducted on apricot trees of Mogador variety, using four doses of foliar boron (ppm) (0-B0, 150-B150, 225-B225 and 300-B300 ppm) and four irrigation levels (100%-I100, 75%-I75, 50%-I50 and 25%-I25 of available water ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
0
0
1
Order By: Relevance
“…Along with these lines of evidence, numerous studies have demonstrated that applying boron and zinc micro-fertilizers can effectively boost crop yields; however, determining the optimal application dose remains crucial for achieving maximum productivity gains. On the other hand, it is worth noting that apricot trees did not exhibit corresponding increases despite these efforts; Berkant et al, for example, found no significant differences in apricot fruit size or yield even with increased doses of boron [38]. While limited research exists regarding using boron and zinc micro-fertilizers on jujube trees, our study's results align with similar experiments conducted on various crops or fruit trees worldwide.…”
Section: Yieldsupporting
confidence: 84%
“…Along with these lines of evidence, numerous studies have demonstrated that applying boron and zinc micro-fertilizers can effectively boost crop yields; however, determining the optimal application dose remains crucial for achieving maximum productivity gains. On the other hand, it is worth noting that apricot trees did not exhibit corresponding increases despite these efforts; Berkant et al, for example, found no significant differences in apricot fruit size or yield even with increased doses of boron [38]. While limited research exists regarding using boron and zinc micro-fertilizers on jujube trees, our study's results align with similar experiments conducted on various crops or fruit trees worldwide.…”
Section: Yieldsupporting
confidence: 84%
“…Bu yüzden olumsuz toprak şartlarına toleransı yüksek olan bitki tür ve çeşitlerini değerlendirmek veya bitki besin maddelerinin birbirleri ile etkileşimlerden faydalanarak bu sorunla başetmek mümkün olacaktır (Soy & Güneş, 2003). Bitki türlerinin yanı sıra türler içindeki genotipler de B gereksinimleri açısından önemli farklılıklar gösterir (Akan ve ark., 2022;Ödemiş & Uncu, 2022). Bir bitki için eksik olan B miktarı, başka bir bitki için toksik olabilmektedir (Brdar-Jokanović, 2020).…”
Section: Introductionunclassified